Regional Press and Local Authority Structures: History of Its Establishment and Relations (1930–2000). On the example of the Omsk Region - S. V. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
In the USSR, the establishment of district newspapers took place on the during the period of the socialist reorganization of the countryside. Adhering to the ideological line of the party leadership, they described in the newspapers the approaches of the party leaders to the solution of not only regional but also national issues. After the collapse of the Soviet political system, temporarily freed the editorial board from the influence of the regional leadership. The refusal of the state to support the mass media caused a negative attitude to the regional leadership of the local leadership and villagers. The regional leadership was forced to create an information and analytical structure of the administration of the Omsk region, with the support of the federal government. They appeared in late 1992 and existed until elections in 1996. Among the forms of influence on regional newspapers there are: — analysis of the content of newspapers in order to determine the attitude of the editorial staff to activities of the regional administration; — training of editors and journalists of district newspapers on thematic courses; — financial support of regional newspapers from the regional and district budget; — preparation of articles and materials of the regional administration. The work of the committee with district newspapers resulted in a victory in the elections to the Legislative Assembly of the Omsk Region in 1995, included representatives of management and business circles who won 25 out of 30 seats. Until 2000, the district newspapers continued to shift to the federal government